THE ROLE OF ENDOTHELIAL CELLS IN THE PROCESS OF ANGIOGENESIS: ANALYSIS OF HISTOLOGICAL STUDIES (KIUT Publication, 2025)
Angiogenesis is the process of forming new capillaries from existing blood vessels based on endothelial activity, playing a crucial role in pregnancy, development, wound healing, and tumor growth. Endothelial cells differentiate into “tip” and “stalk” cells, with filopodia determining the direction of new vessel growth. The proliferation and migration of these cells shape the tissue microenvironment and ensure angiogenesis. Histological and immunohistochemical methods, particularly the use of CD31, CD34, and von Willebrand factor (vWF) markers, are employed to assess angiogenesis through microvessel density (MVD).